2019
DOI: 10.1177/2515816319884937
|View full text |Cite
|
Sign up to set email alerts
|

The vascular effect of glibenclamide: A systematic review

Abstract: Objective: To systematically review the vascular effects of glibenclamide. Background: Infusion of adenosine triphosphate (ATP)-sensitive potassium (KATP) channel opener (KCO) levcromakalim dilates cranial arteries and induces headache and migraine attacks. Recent data show that levcromakalim-induced vasodilation is associated with headache. Glibenclamide is a KATP channel blocker that may alter the vascular tone and thus has an impact on headache or migraine prevention. Methods: A search through PubMed was un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 68 publications
(67 reference statements)
1
11
0
1
Order By: Relevance
“…It is tempting to speculate that the increased headache incidence and intensity 180 min after levcromakalim infusion may be associated with the half-life of glibenclamide and thus, the decrease of plasma glibenclamide concentration. Consistent with previous studies investigating effects of 5–10 mg oral glibenclamide on systemic hemodynamic (17,18,2023), we found no change in HR and MABP after glibenclamide compared to placebo. However, one study reported that oral glibenclamide (10 mg) increased systolic but not diastolic blood pressure compared with placebo (24).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It is tempting to speculate that the increased headache incidence and intensity 180 min after levcromakalim infusion may be associated with the half-life of glibenclamide and thus, the decrease of plasma glibenclamide concentration. Consistent with previous studies investigating effects of 5–10 mg oral glibenclamide on systemic hemodynamic (17,18,2023), we found no change in HR and MABP after glibenclamide compared to placebo. However, one study reported that oral glibenclamide (10 mg) increased systolic but not diastolic blood pressure compared with placebo (24).…”
Section: Discussionsupporting
confidence: 92%
“…In preclinical experiments, glibenclamide attenuated potassium channel openers-induced vascular changes without altering the basal vascular tone (23). A few studies have reported that glibenclamide increased the basal tone in rat dural artery (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…33,34 In preclinical experiments, glibenclamide attenuated KCOs-induced vasodilation without altering the basal vascular tone. 14 Few studies reported that glibenclamide increased the basal tone in rat dural artery, 16,17 and one study reported that glibenclamide had no effect on brain perfusion signals in a rat model of severe ischemia with delayed reperfusion. 6 In the present study, glibenclamide did not alter the in vivo global mean CBF and arterial circumferences.…”
Section: Discussionmentioning
confidence: 99%
“…Different effects of glibenclamide between pre- and posttreatment cannot be applied as both approaches inhibited KCOs-induced vasodilation in preclinical studies. 14 One possible explanation for the lack of glibenclamide effect on vascular changes could be that glibenclamide has less efficacy on SUR2B subunit expressed in the VSMCs compared to SUR1. Another explanation is that the preclinical studies used a high dose which is not applicable for clinical use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation